THE COMPETITIVENESS OF POLISH AGRICULTURE AFTER ACCESSION TO THE EU - Marek, Wigier (Economics of Agriculture, 2014)
The purpose of doing business in agriculture is to achieve the best possible economic effect with the available factors of production. Production factors, which are determined by their quantity and quality, create a definite production potential. Socio-economic transformations that took place in Poland in the period of EU membership caused a number of structural changes in the resources and distribution of production factors in agriculture. As compared to other sectors of the economy the changes in the agricultural sector seem relatively the most significant ones. The material presented below includes: a brief presentation of the place and the role of agriculture in the Polish economy, analysis of structural changes in the 2002-2012 period, information concerning economic results of the agricultural sector and financial dimension of public policies for agriculture and conclusions from this assessment referring to the issues of competitiveness and efficiency of the Polish sector.